Leisure involvement and service-oriented behaviour among frontline SME employees / Adila Sosianika, Tintin Suhaeni and Dwi Suhartanto. - Sosianika, Adila; Suhaeni, Tintin; Suhartanto, Dwi (Universiti Teknologi Mara Selangor, 2020)
Literature suggest the importance of employee leisure involvement towards their service performance. However, empirical investigation assessing the link between employee leisure involvements in predicting employee service-oriented behavior remains scarce. This study inspects the influence of employees’ leisure involvement on their service-oriented behavior. A sample of 451 SME (Small-Medium Enterprise) employees were collected in Bandung, Indonesia. The proposed model was tested using variance-based SEM (PLS). Out of the three dimensions of leisure involvement, only attraction and centrality were found to be a significant predictor for employees’ service-oriented behavior. The dimension of self-expression is not significant in predicting service-oriented behavior. These findings are coherent with sociology studies where a type of employees known as “seekers” prioritizes leisure in their work-related decisions. Conceptual and practical significance of the study is also provided. This study reveals that highly leisure-involved frontline employees are inclined to be satisfied with their life, enabling them to deliver a high service performance.